2014
DOI: 10.4291/wjgp.v5.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post-ERCP pancreatitis

Abstract: Post-procedure pancreatitis is the most common complication of endoscopic retrograde cholangio pancreatography (ERCP) and carries a high morbidity and mortality occurring in at least 3%-5% of all procedures. We reviewed the available literature searching for "ERCP" and "pancreatitis" and "post-ERCP pancreatitis". in PubMed and Medline. This review looks at the diagnosis, risk factors, causes and methods of preventing post-procedure pancreatitis. These include the evidence for patient selection, endoscopic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 88 publications
1
32
0
4
Order By: Relevance
“…Numerous studies have shown that NSAIDs can effectively inhibit the activity of phospholipase A 2 and reduce the incidence of PEP . Recent RCTs and meta‐analyses have shown that NSAIDs can significantly reduce the incidence of PEP in high‐risk patients.…”
Section: Medical Prevention Of Post‐ercp Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that NSAIDs can effectively inhibit the activity of phospholipase A 2 and reduce the incidence of PEP . Recent RCTs and meta‐analyses have shown that NSAIDs can significantly reduce the incidence of PEP in high‐risk patients.…”
Section: Medical Prevention Of Post‐ercp Complicationsmentioning
confidence: 99%
“…Recent RCTs and meta‐analyses have shown that NSAIDs can significantly reduce the incidence of PEP in high‐risk patients. The route of administration and dosage have also been evaluated, showing that rectal administration of NSAIDs within 30 minutes before or after ERCP is effective in preventing PEP, while its oral or intramuscular administration is not . A meta‐analysis of 24 clinical studies concluded that indomethacin and diclofenac could significantly reduce the incidence of mild PEP, although there was no significant reduction in moderate‐to‐severe PEP.…”
Section: Medical Prevention Of Post‐ercp Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andriulli et al[3] conducted a systematic review of 21 selected surveys involving 16855 patients exhibiting a 3.5% incidence of PEP and observed that 0.11% of those patients died. Although many PEP prophylactic treatments have been reported[4-6], only prompt aggressive intravenous hydration is reportedly effective at reducing morbidity and mortality[7-10]. Therefore, early PEP identification is important, as it facilitates early intervention and may prevent disease progression and death.…”
Section: Introductionmentioning
confidence: 99%
“…They may also generate toxic metabolites (like nucleoside reverse transcriptase inhibitors) or induce hypetriglyceridemia (like estrogens), or give an immuno-mediate reaction (like sulfonamides). 17 Drugs inducing pancreatitis are classified in four classes: Ia (drugs with at least one case report, evidence of a positive re-challenge, and exclusion of other causes of AP, such as codeine, cytarabine, dapsone, enalapril, furosemide, isoniazid, mesalamine, metronidazole, pentamidine, pravastatin, simvastatin, sulfamethoxazole, sulindac, tetracycline, valproic acid), Ib (the same but without exclusion of other causes of AP such as amiodarone, azathioprine, dexamethasone, lamivudine, losartan, 6-MP, premarin, trimethoprim-sulfamethoxazole), II (at least four case reports with a consistent latency period for at least 75% of the cases, for example: acetaminophen, clozapine, erythromycin, estrogen, propofol, tamoxifen), III (at least two case reports but without re-challenge data or a consistent latency period, like alendronate, carbamazepine, ceftriaxone, clarithromycin, cyclosporin, hydrochlorothiazide, ribavirin, metformin, minocycline, naproxen, prednisone, prednisolone), and IV (one case report without re-challenge data, for example ampicillin, cisplatin, colchicine, cyclophosphamide, diclofenac, doxorubicin, interleukin-2, octreotide, propoxyphene, rifampin, risperidone, sertraline, tacrolimus, vincristine). The management of the patient with acute pancreatitis Acute pancreatitis has also been reported during therapies with interferon (both in the standard and pegylated form) in patients with chronic hepatitis B and C (in these cases in association with ribavirin), may be due to immune modulation effects of the drug.…”
Section: Etiologymentioning
confidence: 99%